SWOT-АНАЛІЗ: ШЛЯХ ДО СТІЙКОГО РОЗВИТКУ В УМОВАХ НЕВИЗНАЧЕННОСТІ - Ivanenko, Valentyna; Klimova, Inna; Morozov, Vitaly (Zhytomyr Ivan Franko State University, 2024)
SWOT analysis is a strategic planning tool that identifies the internal strengths and weaknesses of an enterprise and external opportunities and threats, while also establishing links between them. It has been proven that a systematic analysis of these four elements allows for a comprehensive understanding of a company's current position, leveraging its strengths, addressing weaknesses, capitalizing on opportunities, and mitigating potential threats. A critical analysis of the advantages and disadvantages of the activities of FPS Flexibles Ukraine, the subject of this study, was conducted. The internal and external environments of the company were analyzed using the SWOT analysis model, focusing on the company's strengths, weaknesses, opportunities, and expected threats. Based on the results of the SWOT analysis, a matrix of measures was developed, outlining three strategic directions for each part of the matrix: leveraging strengths, eliminating weaknesses, capitalizing on opportunities, and mitigating threats. Additionally, an Action Plan was proposed, providing a clear overview of action steps, responsible parties, time frames, and resources required for each strategic objective. This plan facilitates effective implementation and monitoring. Utilizing the proposed strategic framework and action plan will support FPS Flexibles Ukraine LLC's commitment to driving sustainable growth and resilience in an ever-changing business landscape. It will enable the company to not only overcome current challenges but also position itself for long-term success and leadership in the industry. The outcome of this analysis will inform strategic decision-making, helping FPS Flexibles Ukraine LLC to overcome challenges and seize market opportunities while maintaining a strong focus on sustainability.